Hydrologic responses to restored wildfire regimes revealed by soil moisture-vegetation relationships. (February 2018) - Boisramé, Gabrielle; Thompson, Sally; Stephens, Scott
Highlights: 40 years of managed wildfire reduced forest cover in a Sierra Nevada watershed. Vegetation is strongest soil moisture predictor in linear and random forest models. Managed wildfires increased the variability of soil moisture spatial distributions. The most common vegetation transitions had little impact on soil moisture. Localized moisture increases have potential ecological and water resources impacts. Abstract: Many forested mountain watersheds worldwide evolved with frequent fire, which Twentieth Century fire suppression activities eliminated, resulting in unnaturally dense forests with high water demand. Restoration of pre-suppression forest composition and structure through a variety of management activities could improve forest resilience and water yields. This study explores the potential for "managed wildfire", whereby naturally ignited fires are allowed to burn, to alter the water balance. Interest in this type of managed wildfire is increasing, yet its long-term effects on water balance are uncertain. We use soil moisture as a spatially-distributed hydrologic indicator to assess the influence of vegetation, fire history and landscape position on water availability in the Illilouette Creek Basin in Yosemite National Park. Over 6000 manual surface soil moisture measurements were made over a period of three years, and supplemented with continuous soil moisture measurements over the top 1m of soil in three sites. Random forest and linear mixed effects models showed a dominant effect of vegetation type and history of vegetation change on measured soil moisture. Contemporary and historical vegetation maps were used to upscale the soil moisture observations to the basin and infer soil moisture under fire-suppressed conditions. Little change in basin-averaged soil moisture was inferred due to managed wildfire, but the results indicated that large localized increases in soil moisture had occurred, which could have important impacts on local ecology or downstream flows.